2023
DOI: 10.3390/jcm12124113
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Placebo and Nocebo Effects on Experimental and Chronic Pain: State of the Art

Giacomo Rossettini,
Francesco Campaci,
Joel Bialosky
et al.

Abstract: (1) Background: In recent years, placebo and nocebo effects have been extensively documented in different medical conditions, including pain. The scientific literature has provided strong evidence of how the psychosocial context accompanying the treatment administration can influence the therapeutic outcome positively (placebo effects) or negatively (nocebo effects). (2) Methods: This state-of-the-art paper aims to provide an updated overview of placebo and nocebo effects on pain. (3) Results: The most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 173 publications
(264 reference statements)
2
8
0
Order By: Relevance
“…Alternatively, some studies have reported the absence of shared brain activations during the perception of pain (Bingel et al, 2011; Freeman et al, 2015; Fu et al, 2021; Shi et al, 2021; Shih et al, 2019). Similar findings have been reported during pain anticipation, as some areas have been reported to be specifically activated for either placebo or nocebo (Fu et al, 2021; Rossettini et al, 2023) or show opposing valence-dependent responses (Amanzio et al, 2013; Kong et al, 2008; Palermo et al, 2015). However, there is conflicting evidence of shared anticipatory activation for both placebo and nocebo in some areas of the DPMS like the DLPFC and ACC (Amanzio et al, 2013; Amanzio & Palermo, 2019; Colloca & Benedetti, 2007; Frisaldi et al, 2015; Manaï et al, 2019; Palermo et al, 2015; Rossettini et al, 2023; Schmid et al, 2015).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Alternatively, some studies have reported the absence of shared brain activations during the perception of pain (Bingel et al, 2011; Freeman et al, 2015; Fu et al, 2021; Shi et al, 2021; Shih et al, 2019). Similar findings have been reported during pain anticipation, as some areas have been reported to be specifically activated for either placebo or nocebo (Fu et al, 2021; Rossettini et al, 2023) or show opposing valence-dependent responses (Amanzio et al, 2013; Kong et al, 2008; Palermo et al, 2015). However, there is conflicting evidence of shared anticipatory activation for both placebo and nocebo in some areas of the DPMS like the DLPFC and ACC (Amanzio et al, 2013; Amanzio & Palermo, 2019; Colloca & Benedetti, 2007; Frisaldi et al, 2015; Manaï et al, 2019; Palermo et al, 2015; Rossettini et al, 2023; Schmid et al, 2015).…”
Section: Introductionsupporting
confidence: 83%
“…Similar findings have been reported during pain anticipation, as some areas have been reported to be specifically activated for either placebo or nocebo (Fu et al, 2021; Rossettini et al, 2023) or show opposing valence-dependent responses (Amanzio et al, 2013; Kong et al, 2008; Palermo et al, 2015). However, there is conflicting evidence of shared anticipatory activation for both placebo and nocebo in some areas of the DPMS like the DLPFC and ACC (Amanzio et al, 2013; Amanzio & Palermo, 2019; Colloca & Benedetti, 2007; Frisaldi et al, 2015; Manaï et al, 2019; Palermo et al, 2015; Rossettini et al, 2023; Schmid et al, 2015). This illustrates an ongoing debate about whether there is a common neural basis of positive and negative expectations instead of entirely separated representations (Freeman et al, 2015; Fu et al, 2021).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Secondly, the neuromodulation intervention treatment process involves a high level of doctor-patient interaction, which can produce certain neurobiological effects. 70,71 Thirdly, patient expectations are another primary source of the placebo effect for analgesia. [72][73][74][75] A secondary analysis 76 of one study concluded that it may be due to higher expectations of baseline outcomes among subjects in the sham acupuncture group.…”
Section: Main Findingsmentioning
confidence: 99%
“…Moreover, studies have demonstrated the capacity to evoke nocifensive behaviors by exploring specific engrams, which represent the intricate configuration of neural connections associated with a particular memory [149]. These learning processes also modulate nocebo and placebo effects arising in pain treatment through expectations, where prior conditioning and/or suggestion can influence both the exacerbation and alleviation of the patient's pain experience [150][151][152].…”
Section: Cortical Processing: Does the Pain Neuromatrix Really Exist?...mentioning
confidence: 99%